A disciplina da Língua Brasileira de Sinais nos cursos de licenciatura em matemática nas instituições públicas de ensino superior em Boa Vista/RR - Cruz, Carolina Serejo de Souza (2023)
This research emerges from concerns born in 2015 during the supervised internship of the Mathematics Degree course and continues to this day, with my experiences in classrooms, as a teacher with a degree in Mathematics and a deaf student. Furthermore, realizing that teachers with degrees in mathematics are faced with difficulties related to the teaching process and communication through Libras. Given this fact, the objective of the research is to analyze how the subject of Libras has been presented to undergraduate students through the descriptions that make up the syllabuses of the curricular matrices of mathematics degree courses at Public Higher Education Institutions in the municipality of Boa Vista, Roraima. To this end, we opted for a qualitative, descriptive approach, in which the syllabus of the Libras subject was analyzed, according to the curricular matrix included in the PPC of the Mathematics Degree course at three Higher Education Institutions, IFRR, UFRR and UERR . The three institutions were chosen because they offer the Mathematics Degree Course in person, concentrated in the municipality of Boa Vista/RR. For the analyses, PPCs from the three selected institutions were collected, as they contained all the criteria for the Degree in Mathematics course, the curricular matrices and the syllabi. In view of this, the results of the analyzes demonstrate that the teaching knowledge offered in the Libras discipline in the Mathematics Degree course at the three Institutions prioritizes the theoretical part of the history of deaf education and Libras, to the detriment of practical teaching knowledge. of Libras, demonstrating a move away from a syllabus that understands the relationship between theory and practice as intrinsic to the learning process and the training of future graduates. It can be concluded, based on the analyzes carried out in the corpus, that the Higher Education Institutions, IFRR, UFRR and UERR are complying with the mandatory legislation, however, they leave something to be desired in terms of preparing mathematics graduates regarding the teaching of knowledge pedagogical tools for assisting deaf people, of basic Libras communication.